Healing with Polymer Containing Phosphazene of Concrete Exposed to Freezing and Thawing - Tanyildizi, Harun (Amer Concrete Inst, 2021)
This work aims to decrease the damage in concrete caused byfreezing-and-thawing. For this, concrete was healed using the polymer containing phosphazene after the freezing and thawing. The Taguchi method was used to decrease the experimental numbers. The experimental variables were determined as cement dosage, the phosphazene percentage, and curing time. 100 x 100 x 100 mm (3.94 x 3.94 x 3.94 in.) cubes were preparedfor experiments. After demolding, the samples were cured in a water tank at 20 degrees C +/- 2 degrees C (68 degrees F +/- 3.6 degrees F) until the test ages (28, 60, 90, 180, and 365 days) were reached. These samples were then subjected to the freezing-and-thawing cycles. The healing process was conducted to the samples by impregnation with the polymer containing phosphazene after freezing-and-thawing cycles. Lastly, the compressive strength, ultrasonic pulse velocity, and weight change of concretes were determined. Scanning electron microscope, energy-dispersive X-ray spectroscopy, and X-ray powder diffraction analyses were performed to examine the microstructures of the samples. The results showed that the impregnation of polymer containing phosphazene after the freezing-and-thawing increased the strength and durability of the concrete.
Keywords: freezing and thawing; healing; mechanical properties; phosphazene; polymer; strength properties